Self‐Catalytic Growth of β‐Ga2O3 Nanostructures by Chemical Vapor Deposition1. Issue 5 (17th September 2014) - Kumar, Sudheer; Tessarek, Christian; Sarau, George; Christiansen, Silke; Singh, Rajendra
<x xml:space="preserve">Abstract</x> In this work, we have studied the synthesis of single crystalline self‐catalyzed beta gallium oxide (β‐Ga2O3) nanostructures by chemical vapor deposition technique. We have adopted a new approach to grow the nanostructures instead of using conventional foreign metal nano‐catalyst based‐approaches. The as‐grown nanostructures including nanowires and nanosheets (NSHs) were grown on spin‐coated Ga2O3 films. The structural studies such as X‐ray diffraction, Raman and transmission electron microscope (TEM) investigations on the nanostructures showed monoclinic phase of Ga2O3 and single crystalline structure. Furthermore, high‐resolution TEM with a selected area electron diffraction pattern recorded on a single β‐Ga2O3 nanowire and nanosheet verified their single crystalline nature, having [001] as favorable growth direction. The energy dispersive X‐ray spectroscopy‐elemental mapping of as‐grown nanostructures indicated uniform distribution of Ga and O. Cathodoluminescence imaging and spectrum revealed excellent luminescence characteristics of nanostructures with a broad UV‐blue emission band (1.80–4.20 eV nm) centered at 2.64 eV. This study also highlights the growth mechanism of NSHs. These β‐Ga2O3 nanostructures have great potential in nanofunctional devices.